Advancing Evidence-Based Practice in Physical Therapy Settings: Multinational Perspectives on Implementation Strategies and Interventions. Issue 1 (11th August 2016) - Bernhardsson, Susanne; Lynch, Elizabeth; Dizon, Janine Margarita; Fernandes, Jasmin; Gonzalez-Suarez, Consuelo; Lizarondo, Lucylynn; Luker, Julie; Wiles, Louise; Grimmer, Karen
Abstract: It is of critical importance that findings from the wealth of clinical physical therapist research are transferred into clinical practice without unnecessary delays. There is a lack of knowledge about strategies that can be used to effectively implement physical therapist research findings and evidence-based practice (EBP) into everyday clinical practice in different national settings and contexts. The purpose of this article is to contribute to knowledge about effective strategies for implementing EBP that have been studied in different national physical therapy settings. The specific aims of this article are to share experiences and provide a current multinational perspective on different approaches and strategies for implementing EBP and to highlight important considerations and implications for both research and practice. Six research studies from various settings in 3 countries are described and synthesized. Key characteristics of the studies and intervention components are tabulated and mapped to the Cochrane Effective Practice and Organisation of Care taxonomy. Commonalities and differences are presented. The implementation strategies described were: a theory-based guideline implementation tailored to identified barriers and facilitators; a multifaceted EBP training package; journal clubs; a multifaceted strategy comprising contextualized procedures, protocols, and standardized resources; barrier identification, education, audit, feedback, and reminders; and contextualized guidelines. Commonalities were the use of a multifaceted approach, educational measures, and clinical guidelines. Key outcomes across the studies were improved attitudes and increased awareness, knowledge, skills, and confidence in EBP; better access to clinical practice guidelines and other EBP resources; identification of barriers that could be targeted in future implementation activities; earlier referrals; and use of recommended outcome measures. The article can serve as a template for other physical therapist researchers in designing implementation studies, as well as to inform policies and practice for health care managers and decision makers who are looking for ways to implement research findings in their organizations.